2020
DOI: 10.5194/acp-2020-924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of primary and aged wood burning and coal combustion organic aerosols in environmental chamber and its implications for atmospheric aerosols

Abstract: Abstract. Particulate matter (PM) affects visibility, climate, and public health. Organic matter (OM), a uniquely complex portion of PM, can make up more than half of total atmospheric fine PM. We investigated the effect of aging on secondary organic aerosol (SOA) concentration and composition for wood burning (WB) and coal combustion (CC) emissions, two major atmospheric OM sources, using mid-infrared (MIR) spectroscopy and aerosol mass spectrometry (AMS). For this purpose, primary aerosols were injected into… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 74 publications
3
13
0
Order By: Relevance
“…This slope is within the previously reported range (Gilardoni et al, 2009;Russell et al, 2009a, b;Liu et al, 2011) considering collection efficiency of AMS (Yazdani et al, 2020b;Kumar et al, 2018;Canagaratna et al, 2007) and the aerosol volatilization artifacts from PTFE filters (Ruggeri, 2017;Subramanian et al, 2004). Yazdani et al (2020b) reported the AMS the collection efficiency to range between 0.7 and 1.1 for the same experiments. The OM concentrations estimated by both methods indicate the significant enhancement with aging even without particle and vapor wall loss consideration (on average 2.4 and 2.7 times by AMS and MIR, respectively).…”
Section: Ams and Mir Om Mass Concentrationssupporting
confidence: 88%
See 4 more Smart Citations
“…This slope is within the previously reported range (Gilardoni et al, 2009;Russell et al, 2009a, b;Liu et al, 2011) considering collection efficiency of AMS (Yazdani et al, 2020b;Kumar et al, 2018;Canagaratna et al, 2007) and the aerosol volatilization artifacts from PTFE filters (Ruggeri, 2017;Subramanian et al, 2004). Yazdani et al (2020b) reported the AMS the collection efficiency to range between 0.7 and 1.1 for the same experiments. The OM concentrations estimated by both methods indicate the significant enhancement with aging even without particle and vapor wall loss consideration (on average 2.4 and 2.7 times by AMS and MIR, respectively).…”
Section: Ams and Mir Om Mass Concentrationssupporting
confidence: 88%
“…In general, the important FGs highlighted by the VIP scores method are the same ones targeted in past studies of atmospheric aerosols (e.g., Ruthenburg et al, 2014;Russell et al, 2009b) and are consistent with our knowledge of POAs and SOAs related to combustion sources (e.g, Bertrand et al, 2018Bertrand et al, , 2017Yazdani et al, 2020b). In addition, they provide insight into the fraction of the combusted fuel that is important for OM formation (e.g., hydrocarbons in CC).…”
Section: Identifying Fg-ion Fragment Relationshipssupporting
confidence: 81%
See 3 more Smart Citations